MUJERES AFRODESCENDIENTES EN EL SUR DE BRASIL: PERCEPCIONES BAJO LAS DIMENSIONES DE JUSTICIA - Campos Lazo, Angie Edell (2017)
This research aims to analyze the perceptions of Afro-descendant activist women in southern Brazil, based on the analysis of the recognition theory of Nancy Fraser. The research gathers information about the development of the Afro-Brazilian movement and its incidence in the specific area of southern Brazil, as well as the activist dynamics of Afro-Brazilian women in the search for their recognition and respect in the Brazilian region characterized by a strong influence and recognition of its European roots. The theory of the recognition of Nancy Fraser is presented as the theoretical base and platform to analyze the redistribution in the economic sphere, the recognition in the socio-cultural space; the political representation, as well as the emotional realization, this last dimension worked by José Henrique de Faria. The research uses the interpretative descriptive methodology within a qualitative line, with the purpose that through the semi-structured interviews and the analysis of documents, based on the critical analysis of the discourse, the real perception of Afro-Brazilian women of the region in terms of recognition categories. There is evidence of a constant reinvention and resistance of Afro-Brazilian women in the region, as well as the difficulties and invisibility that it represents for their society, racism, classism and sexism that intersect to the position in which woman at a disadvantage compared to the other populations. This also rescues the important role of activist women for their community and for society in general, setting the standard for social, political and economic impact, creating aspirational references for young generations.